Anti-inflammatory and wound healing properties of polyphenolic extracts from strawberry and blackberry fruits - Van de Velde, Franco (2019)
The polyphenolic profiles by HPLC-TOF-MS of strawberry ‘San Andreas’ and blackberry ‘Black Satin’ crude extracts (CE) were analyzed. Anthocyanin-enriched fractions (AEFs) and proanthocyanidin-enriched fractions (PEFs) were prepared, and all samples were probed for in vitro anti-inflammatory and wound healing effects in a LPS-stimulated RAW 264.7 macrophage model and in a skin fibroblast migration and proliferation assay, respectively. Blackberry samples exhibited higher ROS reduction than strawberry's (up to 50% ROS suppression). Berries CEs exhibited 20% inhibition in Cox-2 gene expression, while AEFs and PEFs were inactive at the same concentration. Strawberry AEF and PEF were more active against IL-1β and IL-6 gene expressions than the similar fractions from blackberry, where PEF was more active than AEF (75% suppression by strawberry PEF). Moreover, berry PEFs were the active polyphenol fraction against iNOS gene expression (50% and 65% gen suppression by strawberry and blackberry PEF, respectively), mirroring results of NO synthesis suppression. The cell migration potential of berry polyphenolics was associated with anthocyanins. AEFs showed fibroblast migration around 50% of that registered for the positive control. Results obtained in this work highlight the anti-inflammatory properties of berry polyphenolics, especially due to proanthocyanidins. Moreover, promising results were obtained about the effects of berry anthocyanins on wound healing.